Potensi Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) Pasca Pengalihan dari Pajak Pusat Menjadi Pajak Daerah di Kabupaten Banjar - Tati Inayati; Eny Fahrati (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study was conducted with the aim of knowing thetax  potential and ability of the apparatus in managing PBB-P2 after the transfer from Central Tax to Local Tax in Banjar Regency, and the efforts made by the management to increase the acceptance of PBB-P2. This study uses quantitative descriptive analysys techniques. The data used in this study are secondary data and primary data, secondary data is data on the target and realization of PBB-P2 and Local Tax. While the primary data is data on efforts to increase PBB-P2 revenues. The results of this study showed that the potential of PBB-P2 in Banjar Regency after the transfer in 2014 amounted to IDR6.111.956.879 while the target set by Regional Revenue Office was IDR3.700.000.000 or only 61% of the potential PBB-P2. Analysis results of the apparatus ability shows the contribution indicators in 9,23%, which means that the level of PBB-P2 contribution to Local Taxes is still low. Indicators of effectiveness is 116.43%, which means PBB-P2 is very effective. Then the elasticity indicator shows 2.5 which means that it is elastic or the PBB-P2 growth is sensitive to GRDP growth. It can be concluded that the apparatus is quite capable in managing PBB-P2. Efforts made by the management to increase the acceptance of PBB-P2 include providing counseling either through mass media or directly, and also through services with mobile and door-to-door programs.